Economics of prescription of medicines in Pakistan; market failure or executive decision. Points to ponder for improving prescription practices. - Shahzad Ali Khan (Journal of the Pakistan Medical Association, 2024)
The laws of economics oversee the interplay between price of a commodity and how prices affect the demand of that commodity. A logical condition is assumed while studying the impact of price on demand, which believes that “everything else must remain constant”. However, in a real-world scenario there is no such thing as “constant”. It’s an ever-changing world and there are so many variables to consider while making any assumption. Healthcare market is unique in the sense that no other market has so much difference in the knowledge of client (patient) versus the supplier (doctor). This difference creates another phenomenon, called “supplier-induceddemand” where the client must follow all the instructions of the supplier diligently. This phenomenon not only creates the demand of prescribing physician (number of visits, follow ups) but also it generates the demand of other players in healthcare market. The physician may ask clients to purchase any medicine, or a specific brand of the medicine, get tests done from a specific diagnostic centre or seek admission in a specific health facility for treatment or surgery. This makes healthcare market highly imperfect and creates failures in some of the basic assumption of economics.1 Given the nature of healthcare clients, coming to seek health, mostly in a life-or-death situation, assumption of rational decision making may not also hold true. These patients or their relatives are willing to do anything to alleviate pain and suffering and to save their lives or the lives of their loved ones. In such a condition there are chances of market failure when supplier has greatest advantage over the consumer and can make the market shift towards supplier’s own benefits. Even if the notion of ethical practice by physician is believed to be normal, there are conditions where huge market imperfections result in supplier-driven-demand in vogue.2 Continued..